The Development and Modernization of Bachelor Curriculum of Faculty of Dentisary University of Gezira, 2012 - Yousif, Mogahid Adelrhman; Elmobak, Abdelhamed Hasen; Elmobak, Abdelhamed Hasen; Ahmed, Kamal M; Ahmed, Sahla M; Bakri, Nahla; Naser, Eglal Basher; Omer, Sawsen Ahmed (مجلة الجزيرة للعلوم الصحية; مجلد 11 عدد 2 (2015), 2015)
The project of: The Development and Modernization of Bachelor Curriculum of Faculty of Dentisary University of Gezira is sponsored by the Islamic Bank for Development Jeddah and Ministry of Finance Sudan and has been launched in December 2011. The Vice Chancellor of the University of Gezira formed a committee to manage the whole task of development of curricula for all faculties in agricultural and health sectors.